Suppression of Soft Tissue Sarcoma Growth by a Host Defense-Like Lytic Peptide - Steinstraesser, Lars (Public Library of Science, 2011)
BACKGROUND: Soft tissue sarcoma (STS) is an anatomically and histologically heterogeneous neoplasia that shares a putative mesenchymal cell origin. The treatment with common chemotherapeutics is still unsatisfying because of association with poor response rates. Although evidence is accumulating for potent oncolytic activity of host defense peptides (HDPs), their potential therapeutic use is often limited by poor bioavailability and inactivation in serum. Therefore, we tested the designer host defense-like lytic D,L-amino acid peptide [D]-K(3)H(3)L(9) on two STS cell lines in vitro and also in an athymic and syngeneic mouse model. In recent studies the peptide could show selectivity against prostate carcinoma cells and also an active state in serum. METHODS: In vitro the human synovial sarcoma cell line SW982, the murine fibrosarcoma cell line BFS-1 and primary human fibroblasts as a control were exposed to [D]-K(3)H(3)L(9), a 15mer D,L-amino acid designer HDP. Cell vitality in physiological and acidic conditions (MTT-assay), cell growth (BrdU) and DNA-fragmentation (TUNEL) were investigated. Membrane damage at different time points could be analyzed with LDH assay. An antibody against the tested peptide and recordings using scanning electron microscopy could give an inside in the mode of action. In vivo [D]-K(3)H(3)L(9) was administered intratumorally in an athymic and syngeneic (immunocompetent) mouse model with SW982 and BFS-1 cells, respectively. After three weeks tumor sections were histologically analyzed. RESULTS: The peptide exerts rapid and high significant cytotoxicity and antiproliferating activity against the malignant cell lines, apparently via a membrane disrupting mode of action. The local intratumoral administration of [D]-K(3)H(3)L(9) in the athymic and syngeneic mice models significantly inhibited tumor progression. The histological analyses of the tumor sections revealed a significant antiproliferative, antiangiogenic activity of the treatment group. CONCLUSION: These findings demonstrate the in vitro and in vivo oncolytic activity of [D]-K(3)H(3)L(9) in athymic and syngeneic mouse models.